Covering the crucifix and other sacred images - Mumbai Archive Project Team (Jio Institute, 2024)
In the last two weeks of Lent, known as Passiontide, the focus is on Christ’s suffering. Covering the crucifix and other sacred images during this period intensifies this emphasis on the Passion narrative. Veiling the crucifix directs the faithful’s attention toward Scripture readings and Lenten rituals, encouraging a deeper engagement with the Word of God.